Registry report on prediction by Pocock cardiovascular score of cerebral microemboli acutely following carotid endarterectomy. Issue 3 (9th March 2018) - Saedon, Mahmud; Saratzis, Athanasios; Lee, Rachel W S; Hutchinson, Charles E; Imray, Christopher H E; Singer, Donald R J
Abstract : Background: Cerebral microemboli may lead to ischaemic neurological complications after carotid endarterectomy (CEA). The association between classical cardiovascular risk factors and acute cerebral microemboli following carotid surgery has not been studied. The aim of this study was to explore whether an established cardiovascular risk score (Pocock score) predicts the presence of cerebral microemboli acutely after CEA. Subjects and methods: Pocock scores were assessed for the 670 patients from the Carotid Surgery Registry (age 71±1 (SEM) years, 474 (71%) male, 652 (97%) Caucasian) managed from January 2002 to December 2012 in the Regional Vascular Centre at University Hospitals Coventry and Warwickshire NHS Trust, which serves a population of 950 000. CEA was undertaken in 474 (71%) patients for symptomatic carotid stenosis and in 196 (25%) asymptomatic patients during the same period. 74% of patients were hypertensive, 71% were smokers and 49% had hypercholesterolaemia. Results: A high Pocock score (≥2.3%) was significantly associated with evidence of cerebral microemboli acutely following CEA (P=0.039, Mann-Whitney (MW) test). A Pocock score (≥2.3%) did not predict patients who required additional antiplatelet therapy (microemboli signal (MES) rate >50 hour -1 : P=0.164, MW test). Receiver operating characteristic analysis also showed that the Pocock score predicts acute postoperative microemboli (area under the curve (AUC) 0.546, 95% CI 0.502 to 0.590, P=0.039) but not a high rate of postoperative microemboli (MES >50 hour −1 : AUC 0.546, 95% CI 0.482 to 0.610, P=0.164). A Pocock score ≥2.3% showed a sensitivity of 74% for the presence of acute postoperative cerebral microemboli. A Pocock score ≥2.3% also showed a sensitivity of 77% and a negative predictive value of 90% for patients who developed a high microembolic rate >50 hour −1 after carotid surgery. Conclusion: These findings demonstrate that the Pocock score could be used as a clinical tool to identify patients at high risk of developing acute postoperative microemboli.